Advancing CAR-based immunotherapies in solid tumors: CAR- macrophages and neutrophils - Liang, Yanling; Xu, Qumiao; Gao, Qianqian (Frontiers in Immunology, 2023)
Macrophages and neutrophils are the main components of the innate immune system and play important roles in promoting angiogenesis, extracellular matrix remodeling, cancer cell proliferation, and metastasis in the tumor microenvironment (TME). They can also be harnessed to mediate cytotoxic tumor killing effects and orchestrate effective anti-tumor immune responses with proper stimulation and modification. Therefore, macrophages and neutrophils have strong potential in cancer immunotherapy. In this review, we briefly outlined the applications of macrophages or neutrophils in adoptive cell therapies, and focused on chimeric antigen receptor (CAR)engineered macrophages (CAR-Ms) and neutrophils (CAR-Ns). We summarized the construction strategies, the preclinical and clinical studies of CAR-Ms and CAR-Ns. In the end, we briefly discussed the limitations and challenges of CAR-Ms and CAR-Ns, as well as future research directions to extend their applications in treating solid tumors.